2019
DOI: 10.1002/jnr.24558
|View full text |Cite
|
Sign up to set email alerts
|

Proteostasis network alteration in lysosomal storage disorders: Insights from the mouse model of Krabbe disease

Abstract: In Krabbe disease, a mutation in GALC gene causes widespread demyelination determining cell death by apoptosis, mainly in oligodendrocytes and Schwann cells. Less is known on the molecular mechanisms induced by this deficiency. Here, we report an impairment in protein synthesis and degradation and in proteasomal clearance with a potential accumulation of the misfolded proteins and induction of the endoplasmic reticulum stress in the brain of 6-day-old twitcher mice (TM) (model of Krabbe disease). In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Subsequently, our group worked on a BAL comparison between familial and sporadic IPF. Functional analysis showed that ER stress played a central pathogenic role in familial IPF, confirming that the translation of a genetic variant or dysregulated fatty acids [ 29 ] could lead to the engorgement of the endothelial reticulum (ER) [ 36 , 37 ]. On the other hand, proteins up-regulated in the sporadic IPF group were particularly involved in oxidative stress response, as reported previously [ 19 ].…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
“…Subsequently, our group worked on a BAL comparison between familial and sporadic IPF. Functional analysis showed that ER stress played a central pathogenic role in familial IPF, confirming that the translation of a genetic variant or dysregulated fatty acids [ 29 ] could lead to the engorgement of the endothelial reticulum (ER) [ 36 , 37 ]. On the other hand, proteins up-regulated in the sporadic IPF group were particularly involved in oxidative stress response, as reported previously [ 19 ].…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
“…2D electrophoresis was carried out as previously reported [ 20 , 21 ]; briefly, 30 μg of total proteins from each sample were resuspended in rehydration solution; the samples were mixed with 0.2 % immobilized pH gradient buffer (immobilized pH gradient, IPG, GE Healthcare, Uppsala, Sweden) and then loaded onto Immobiline Dry-Strips with immobilized nonlinear pH gradient, ranging from pH 3 to 11 (GE Healthcare, Uppsala, Sweden). Runs were carried out using an Ettan™ IPGphor™ system (GE Healthcare, Uppsala, Sweden) at 16 °C.…”
Section: Methodsmentioning
confidence: 99%
“…This is an important aspect to be considered in ERT as compared to a relatively even tissue distribution of small molecules, including the central nervous system, in chaperone therapy. This is the main reason that the number of reports on approaches to the brain is increasing in recent years for lysosomal diseases [71][72][73][74][75].…”
Section: Future Prospect Of Chaperone Therapymentioning
confidence: 99%